Shirinova, Konul - (:unkn) unknown (My University, 2026)
Konul Nadir Shirinova graduated from Azerbaijan University of Languages, earning a Bachelor's degree in Linguistics in 1998 and a Master's degree in Linguistics in 2000. Since 1997, she has worked at the Azerbaijan University of Architecture and Construction, holding various positions within the International Relations Office. Since 2025, she has served as the Head of the International Joint Education Programs Management Sector. Since 2007, she has also been teaching German as a foreign language at AzUAC. She participated in the EU TEMPUS Project on Energy Management (2005–2008) and completed a professional development programme for German language teachers at the Goethe-Institut in Munich in 2011. She is the author of one textbook and co-author of several scientific publications. Her professional interests include international academic cooperation, student and staff mobility, joint and dual degree programmes, foreign language teaching, and the internationalization of higher education.